2005
DOI: 10.1016/j.jhsb.2005.02.012
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Wrist Ganglia in an Asymptomatic Population: Magnetic Resonance Evaluation

Abstract: Magnetic resonance imaging (MRI) was performed on the wrists of 103 asymptomatic volunteers. The images were evaluated independently by two musculoskeletal radiologists and one orthopaedic surgeon. Wrist ganglia were identified in 53 out of the 103 wrists. The average long and short axes measurements were 8 mm (range 3-22) and 3 mm (range 2-10), respectively. Seventy per cent of the ganglia originated from the palmar capsule in the region of the interval between the radioscaphocapitate ligament and the long ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 17 publications
1
36
1
1
Order By: Relevance
“…Seventy percent of the detected ganglions were located on the volar side of the wrist. 23 This study provides evidence that ganglions can also be found in asymptomatic patients. Consequently, the incidence of ganglions in the general population is higher than calculated on the basis of the analysis of available clinical data on patients treated for symptomatic cysts.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Seventy percent of the detected ganglions were located on the volar side of the wrist. 23 This study provides evidence that ganglions can also be found in asymptomatic patients. Consequently, the incidence of ganglions in the general population is higher than calculated on the basis of the analysis of available clinical data on patients treated for symptomatic cysts.…”
Section: Discussionsupporting
confidence: 51%
“…At least several theories aimed at explaining ganglion pathophysiology exist but all of them have certain weaknesses. 12,15,[23][24][25][26] The first of these theories suggests that a ganglion is a herniation of the joint capsule (herniation of the synovial tissue from the joint). According to this concept, the fluid filling the cyst would originate from the joint and would be pumped into the cyst through a one-way valve mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Whereas magnetic resonance imaging surveillance of asymptomatic individuals has identified a prevalence of greater than 50%, the vast majority of clinically silent cases were volar, with 14% arising from the dorsal carpus. 10 In contrast, the majority of symptomatic wrist ganglions are dorsal, most often arising from the scapholunate interosseous ligament. 10 Although most patients complain of some degree of discomfort, 11 symptoms from a dorsal wrist ganglion are generally reported as mild or minimal.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, the majority of symptomatic wrist ganglions are dorsal, most often arising from the scapholunate interosseous ligament. 10 Although most patients complain of some degree of discomfort, 11 symptoms from a dorsal wrist ganglion are generally reported as mild or minimal. Tomlinson and Field 5 surveyed patients presenting for common benign conditions of the hand.…”
Section: Discussionmentioning
confidence: 99%